The Influence of Leadership Style, Organizational Culture, and Job Satisfaction on Employee Performance - M Jamaludin; Didik Subiyanto (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The Environmental Agency is one of the local government agencies of Bantul Regency, which is in charge of preparing, implementing, supervising, controlling, and controlling all policies specific to the environment in Bantul Regency. This study aims to analyze and determine the influence of leadership style, organizational culture, and job satisfaction on employee performance. This research is quantitative with primary data. While obtaining data, research instruments that have been determined with distribution questionnaires, checks, or checklists are used for respondents. This study used a saturated sample where 105 employees used the entire population of members. The results showed that leadership style has a positive and significant effect on employee performance, organizational culture has a positive and significant impact on employee performance, and job satisfaction has a positive and significant impact on employee performance. The results of the f test stated that leadership style, organizational culture, and job satisfaction simultaneously affect employee performance Keywords : Leadership Style, Organizational Culture, And Job Satisfaction On Employee Performance